2007
DOI: 10.1007/s00213-007-0960-3
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally persistent latent inhibition induced by MK801 is reversed by risperidone and by positive modulators of NMDA receptor function: differential efficacy depending on the stage of the task at which they are administered

Abstract: These results support the validity of MK801-induced persistent LI as a model of negative/cognitive symptoms in SZ and indicate that this model may have a unique capacity to discriminate between typical APDs, atypical APDs, and glycinergic compounds, and thus, foster the identification of novel treatments for SZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 99 publications
8
25
1
Order By: Relevance
“…In this model, AVE1625 reversed neurodevelopmentally induced abnormally persistent LI. Previous studies using the L-NoArg model have shown that the abnormal behaviors in this model are reversed by procognitive agents and atypical antipsychotics Black et al 2009;Gaisler-Salomon and Weiner 2003;Gaisler-Salomon et al 2008). Such activity therefore strengthens the case for AVE1625 as a potentially effective treatment in the cognitive domain of schizophrenia.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In this model, AVE1625 reversed neurodevelopmentally induced abnormally persistent LI. Previous studies using the L-NoArg model have shown that the abnormal behaviors in this model are reversed by procognitive agents and atypical antipsychotics Black et al 2009;Gaisler-Salomon and Weiner 2003;Gaisler-Salomon et al 2008). Such activity therefore strengthens the case for AVE1625 as a potentially effective treatment in the cognitive domain of schizophrenia.…”
Section: Discussionmentioning
confidence: 62%
“…Reversal of NMDA antagonist-induced abnormally persistent LI is believed to reflect potential therapeutic activity for negative symptoms of schizophrenia and Gaisler-Salomon and Weiner 2003;Gaisler-Salomon et al 2008). In this model, AVE1625 attenuated MK-801-induced persistent LI, therefore further supporting a potential procognitive profile for AVE1625.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanisms underlying the effects of SSR180711 seen here remain to be investigated, our results demonstrate that this agent possesses in the LI model a behavioral profile of atypical APDs, which consists of LI potentiation when given on their own, reversal of amphetamine-induced disrupted LI and reversal of MK801-induced persistent LI (Gaisler-Salomon et al, 2008;Gaisler-Salomon and Weiner, 2003;Lipina et al, 2005;Shadach et al, 2000;Weiner, 2003). This is unlike the typical APDs, which fail to reverse MK801-induced LI persistence.…”
Section: Ssr180711-behavioral and Psychological Profilementioning
confidence: 52%
“…For example, blockade of NMDA receptors during conditioning results in persistent latent inhibition (i.e., latent inhibition is expressed under conditions in which stronger conditioning typically overcomes the effects of CS pre-exposure) (Gaisler-Salomon and Weiner 2003). DCS injected before conditioning effectively disrupts this persistent latent inhibition induced by blockade of NMDA receptors (Gaisler-Salomon et al 2008). Nonetheless, there was no evidence here to support the possibility that learned inattention to the CS is causal to DCS facilitation of extinction retention.…”
Section: Discussionmentioning
confidence: 79%